Design and Fabrication of Biodegradable Antenna Using Jute Material for UWB Application - Kinol. A. Mary Joy; Marshiana Devaerakkam; D. Godwin Immanuel; Krishnamoorthy Narasu Raghavan; Grace Kanmani Prince; Kassu negash (Advances in Materials Science and Engineering)
Ultra-Large Band (UWB) is a radio technology used for the transmission and distribution of radio energy over a wide frequency band with low power spectral density. A newer UWB Microstrip patch antenna is designed using a jute material as a substrate because of its durability and CO2 and water footprint. The ecological impact is relatively small with Cradle to Cradle, biodegradable with 100% compostable, and extremely strong. The jute substrate is reinforced to make it nonflexible and hydrophobic for further better electrical and mechanical properties, and it is treated with the conductive polymer sodium alginate; the results were compared with the raw hydrophilic jute substrate. The proposed antenna design and results were compared with the similar antenna using the FR4 substrate of a dielectric constant of 4.4 and a thickness of 1.6, and the ultra-wideband spectrum range from 3.1 to 10.6 GHz. It is used for both uplink and downlink transmission of local area network (LAN), wide area network (WAN), and satellite communications spectrum (SCP). The performance of this network provides a wider bandwidth transmission for the range of 1 to 14 GHz applications.